The Effectiveness of Pjbl by Using Reused Paper on Nervous System Concept - Nofitasari, Maria Ulfa; Widiatningrum, Talitha (Journal of Biology Education, 2019)
This study aims to determine the effectiveness of project based learning model by using reused paper on neuron system lesson to students learning outcomes in SMA Negeri 1 Pemalang. This study used pretest-posttest control group design. The samples that were used are the third mathematics and scince major of eleventh-graders students (control class) and eleventh-graders of the fourth mathematics and science major (experimental class). The samples were taken by cluster random sampling technique. The results show that the learning outcomes in the experimental class are better than control class. The average of students’ N-gain score in the experimental class was significantly different with control class and it was higher than control class (0,72 > 0,58), the average of experimental’s class psychomotor learning outcomes was classified in the very good category, the experimental’s class affective learning outcomes (environmental care attitude) was significantly different with control class and it was greater than the control class (82> 63). This result is supported by students' and teachers' positive responses of project based learning model by using reused paper. Based on this stufy results, it is concluded that the implementation of project based learning model by using reused paper was effectively optimizing students learning outcomes on neuron system material.